Effectiveness of Using Center and Circle Methods to Increase Interest in Learning Early in Children - Titik Mulat Widyastuti; Syahria Anggita Sakti (Universitas Nahdlatul Ulama Surabaya, 2022)
The purpose of this study was to determine the effectiveness of the Center and Circle method as an effort to increase interest in early childhood learning. The research subjects were children in KB TK Almutaqin Yogyakarta. The results showed that there were differences in interest in learning before and after getting the Center and Circle method. This is indicated by the results of the t=-4,735 and p=0,000 test (p<0,05). The average interest in learning for students before receiving treatment with the center and circle method was 1,667, while the average after receiving treatment with the center and circle method was 5,600. This confirms that the Sentra and Circle methods are effective in increasing children's interest in learning at KB Almutaqin Kindergarten, Sleman Yogyakarta.